Evidence-based management: helping managers make better decisions - Rousseau, Denise M. (Henry Stewart Talks, 2012)
Evidence-based management definition, Example of Chesley Sullenberger (USAIR), Zeitgeist, Overcoming limits of unaided decisions, How to practice evidence-based management
Reviewed at 2019/10/31